Komunikasi Pemasaran Terpadu “Lemospirés Batik” dalam Menarik Minat Pembelian Konsumen - Cindy Andita Kirana (Jurnal Ilmu Komunikasi, 2019)
This article examines the marketing communication strategies used by Lemospirés Batik to attract consumer interest. This research uses a qualitative-descriptive approach. The research data were analyzed with the perspective of the marketing communication mix theory. The results of this study describe that the strategy taken by Lemospirés Batik to market and introduce its products is (1) the use of advertisements on social and non-social media, (2) organizing exhibitions to do direct marketing, (3) giving discounts and giveaways. to create sales promotions, (4) creating distinctive features on products that are part of personal selling, (5) using public relations to build relationships, and (6) using social media Instagram and Facebook to market products with the concept of storytelling.